Critical Thinking Ability in EFL Students' Argumentative Essay Writing: The Difficulties and The Strategies - Wawat Srinawati; Rahmawati Alwi (JURNAL SERAMBI ILMU, 2020)
The aim of research is to explore the effect, if any, of integrating critical thinking on learners’ use of critical thinking skills in argumentative writing. The research used quasi-experimental desaign, it is include control group and experimental group. The data which has been quantitatively analyzed indicates that the experimental group significantly outperformed the control group. The students’ ability to use more credible evidence, address alternative arguments, support conclusions, and maintain the logical flow of ideas in their essays did not reach a mastery level in the posttest, yet the average level they reached is reassuring in view of the short time of the training they had. The integration of critical thinking for longer periods may bring forth encouraging outcomes. Argumentative writing constitutes an important part of second-language learners' academic writing. Data analysis indicated that most participants perceived the rhetorical aspects of English argumentative writing as difficult. Data analysis also indicated that participants mainly used cognitive, social, and search strategies, whereas metacognitive strategies were used infrequently. Potential implications of the study for second-language writing instruction are discussed